Sistem Pendukung Keputusan Penentuan Berita Hoax Dengan Menggunakan Logika Fuzzy - Christina Aritonang; Murni Marbun (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
Social media is one of the diversity of information offered and flexibility in forming friendship connections. Everyone has freedom of opinion on a worldwide basis. The number of people who are not responsible for sharing hoax news with the intention of provoking their opponents. This study supports the decision to determine hoax news and determines hoax news by applying the Fuzzy Logic of the mamdani method using the programming language used in making applications, namely Web, Database and MySql. The criteria supporting the decision to determine hoax news are Spread, Media Literacy, Significance and Certainty. So it can be concluded that the hoax news level is at 11,824 or is categorized as MEDIUM